(untitled) (Nigerian Journal of Technology, 2025)
An incomplete construction project contract affects the early completion of construction projects, leading to abandonment. Hence, this study assessed the factors contributing to the incomplete construction project contracts in Lagos, Nigeria. A quantitative research design was used, and questionnaire was designed to retrieve data from the respondents. Two hundred and ninety-three questionnaires (87.5 %) were retrieved, distributed through Google Forms to the respondents in Lagos, Nigeria. Descriptive and exploratory factor analysis were used in analyzing the data retrieved. A one-way ANOVA test and a Least Square Design (LSD) posthoc test was also used to measure the significant difference between group responses. The principal component analysis findings established four components of factors contributing to incomplete construction project contracts: 1) inadequacy, 2) vagueness of project parties’ responsibilities, 3) indecisiveness and 4) renegotiation. The study’s practical implications provide construction companies with a benchmark to measure their performance against industry standards on construction project contract management, helping them set realistic goals and identify areas of incompleteness for continuous improvement.